Sifat Fisiko-Kimia Mayonnaise dengan Berbagai Tingkat Konsentrasi Minyak Nabati dan Kuning Telur Ayam Buras - Dedes Amertaningtyas; Firman Jaya (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2011)
Abstract : The objective of current research was to find out the precise combination between concentrations of vegetable oils (65%; 70%; 75%) and chicken egg of local chicken (6%; 9% and 12%) which produced mayonnaise with a good quality of physico-chemical properties. The results showed that the combination of concentration of vegetable oils and chicken egg of local chicken gave the difference significant on viscosity, moisture content and protein, however, has no effect on pH. The best treatment obtained from a combination of vegetable oil 75% concentration by concentration of chicken egg of local chicken 9% Keywords : Physico-chemical properties, Mayonnaise, Vegetable Oils and Egg, of Local Chicken